The role of participatory leadership in promoting workplace spirituality: (An exploratory study of the opinions of a group of teachers in the faculties of administration and economics and the College of Education for Human Sciences at the University of - Majeed al Nasrawe, Adil (Iraqi Journal for Administrative Sciences, 2024)
The study aimed and focused on the intellectual and scientific controversy that was raised in the study problem to know the role of participatory leadership for workers in the faculties of administration and economics and the College of Education for Human Sciences at the University of Karbala with its dimensions (participation in decision-making, delegation of authority, human relations), And its impact on the spirituality of the workplace with its dimensions (involvement in work, feeling in the group, spiritual communication). The problem of the study was raised through questions, the most important of which is what is the degree of participatory leadership and the spirituality of the workplace, and what is the level of the relationship and influence between them in the faculties under study In order to reach the goal for which the study was prepared and to test its hypotheses, a questionnaire was prepared and adapted to suit the work in the university and its faculties under study. The researcher relied on a sample of (123) people, according to the nature of their work. The data were analyzed using the SPSS.23 statistical program and using the Alpha-Cro-Nbach coefficient to test the validity and reliability. The PEARSON simple correlation matrix was used to test the hypotheses. The researcher concluded that there is a strong direct correlation between the two variables, which indicates a high awareness and awareness of the concept of participatory leadership among university employees, which enhances the spirituality of the workplace.